Tourism Climate Index under Climate Change Scenarios: Aegean and Mediterranean Regions - Cilek, Muge Unal (VDE VERLAG GMBH, 2022)
All technological developments aim to provide individuals with a more comfortable life. Thermal comfort, consisting of climatic conditions in which heat exchange between the human body and the environment is balanced, gains importance in planning studies. In this study, the most suitable time for sea tourism in the Mediterranean and Aegean regions and how the most suitable tourism areas will change with climate change are modelled using the Tourism Climate Index (TCI). The model uses the mean temperature, relative humidity, total precipitation, and wind data produced for the present and future. The results show that in the present situation, tourism climate is comfortable for the whole region between April and November; however, in the future scenario, according to Shared Socioeconomic Pathway SSP5-8.5, 70% of the area will be uncomfortable for tourism activities from June to August. These results will significantly contribute to creating a climate-based tourism strategy for Turkey. © Wichmann Verlag, VDE VERLAG GMBH.
Keywords: climate change; Mediterranean Turkey; Thermal comfort; tourism climate; tourism planning